Shifting niches of marine predators due to human exploitation: The diet of the South American sea lion (Otaria flavescens) since the late Holocene as a case study - Zenteno, Lisette; Borella, Florencia; Gomez Otero, Julieta; Piana, Ernesto Luis; Belardi, Juan Bautista; Borrero, Luis Alberto; Saporiti, Fabiana; Cardona, Luis; Crespo, Enrique Alberto (Cambridge University Press, 2015)
Stable isotope ratios of carbon and nitrogen in archaeological and modern bone samples havebeen used to reconstruct the dietary changes of the South American sea lion Otaria flavescens from the late Holocene to the present in the southwestern Atlantic. We sampled bones from archaeological sites in northern-central and southern Patagonia, Argentina, and bones housed in modern scientific collections. Additionally, we analyzed the stable isotope ratios in ancient and modern shells of intertidal molluscs to explore changes in the isotope baseline and allowcomparison between bone samples from different periods after correction for baseline shifts. Results confirmed the trophic plasticity of the South American sea lion, demonstrated the much larger impact ofmodern exploitation of marine resources as compared with that of hunter-gatherers, and underscored the dissimilarity between the past and modern niches of exploited species. These conclusions are supported by the rather stable diet of SouthAmerican sea lions during severalmillennia of aboriginal exploitation, in both northern-central and southern Patagonia, and the dramatic increase in trophic level observed during the twentieth century. The recent increase in trophic levelmight be related to the smaller population size resulting from modern sealing and the resulting reduced intraspecific competition. These results demonstrate how much can be learned about the ecology of modern species thanks to retrospective studies beyond the current, anthropogenically modified setting where ecosystem structure is totally different from that in the pristine environments where current species evolved.